2017
DOI: 10.1590/1519-6984.172230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of replacing fish meal by a mixture of different plant protein sources on the growth performance in Nile Tilapia (Oreochromis niloticus L.) diets

Abstract: The present study aimed to assess the appropriate level of replacement of fish meal (FM) with alternative plant sources in the feed fed to Oreochromis niloticus to evaluate the growth performance. Three isoproteinious (40% crude protein) diets were prepared from different ingredients viz., fish meal, corn gluten meal, wheat gluten meal, and bagasse kenna meal. O. niloticus showed a maximum increase in weight as 9. 70, 11.09, 8.53 and 8.32 fortnight with feeding treatment A, B, C and D, respectively. The grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Current findings also found that Oreochromis sp fed with BSFM in combination with MEM had significantly better growth performance and feed efficiency. This result is similar to past research revealed that replacing fish meal by a mixture of different plant protein sources showed better growth performance in Nile Tilapia (Oreochromis niloticus L.) (Al-Thobaiti et al, 2018). Some studies also revealed that the used of soybean meal (Mo et al, 2016), cotton seed meal (Yu et al, 2014), seaweed (Gracillaria arcuate) (Al-Asgah et al, 2016) have significant effects on the growth of fish.…”
Section: Resultssupporting
confidence: 90%
“…Current findings also found that Oreochromis sp fed with BSFM in combination with MEM had significantly better growth performance and feed efficiency. This result is similar to past research revealed that replacing fish meal by a mixture of different plant protein sources showed better growth performance in Nile Tilapia (Oreochromis niloticus L.) (Al-Thobaiti et al, 2018). Some studies also revealed that the used of soybean meal (Mo et al, 2016), cotton seed meal (Yu et al, 2014), seaweed (Gracillaria arcuate) (Al-Asgah et al, 2016) have significant effects on the growth of fish.…”
Section: Resultssupporting
confidence: 90%
“…Ingredients in aquafeed formulations significantly affect certain ratios of diet proximate composition. Hence, it is important to accurately formulate diets when different lipid levels are supplemented in fish diets (Al-Thobaiti et al, 2017). This study used formulations with a balanced profile intended to satisfy the nutritional requirements of Petenia splendida.…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Thobaiti et al . () evaluated the substitution of fish meal by a mixture of plant protein sources (soya bean meal, corn gluten meal and wheat gluten meal) on the growth performance in Nile Tilapia ( Oreochromis niloticus L.). The results showed that the fish meal can be replaced up to 20% by a mixture of plant protein without negative impact on weight gain, SGR, FCR, protein efficiency ratio and fish health.…”
Section: Sources Of Proteinmentioning
confidence: 99%